2015
DOI: 10.1152/ajpregu.00495.2014
|View full text |Cite
|
Sign up to set email alerts
|

IUGR increases chromatin-remodeling factor Brg1 expression and binding to GR exon 1.7 promoter in newborn male rat hippocampus

Abstract: Ke X, McKnight RA, Maniar LE, Sun Y, Callaway CW, Majnik A, Lane RH, Cohen SS. IUGR increases chromatin-remodeling factor Brg1 expression and binding to GR exon 1.7 promoter in newborn male rat hippocampus. Am J Physiol Regul Integr Comp Physiol 309: R119 -R127, 2015. First published May 13, 2015 doi:10.1152/ajpregu.00495.2014.-Intrauterine growth restriction (IUGR) increases the risk for neurodevelopment delay and neuroendocrine reprogramming in both humans and rats. Neuroendocrine reprogramming involves th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…This fetal programming is associated with epigenomic alterations 15 and has been demonstrated to occur across multiple generations. 1217 Therefore, the identification of effective interventions during gestation to stop the cycle of the adult onset of disease is essential to ameliorate not only the health of the individual, but that of future generations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fetal programming is associated with epigenomic alterations 15 and has been demonstrated to occur across multiple generations. 1217 Therefore, the identification of effective interventions during gestation to stop the cycle of the adult onset of disease is essential to ameliorate not only the health of the individual, but that of future generations.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that IUGR is associated with epigenetic alterations in many tissues including liver. 1215, 5, 16, 17 Methylation levels are sensitive to the availability of the nutrients in the one carbon metabolism pathway including methionine, folic acid and choline. 18 We therefore hypothesize that supplementation of the maternal diet with components of the one carbon metabolism pathway during gestation would be associated with changes in gene-specific DNA methylation levels in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, just as there are data that prenatal stressors and IUGR are associated with epigenetic modifications, there is evidence that the beneficial effects of physical activity are mediated through epigenetic modifications. [50][51][52][53][54][55] We speculate that IUGR may mediate epigenetic changes to genes involved in cardiorespiratory fitness, which may obscure response to exercise regimens. IUGR may act as a primary insult initiating epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The list of nutrients identified to cause changes to DNA methylation in early life has been growing. These early Intrauterine growth restriction H4K20 histone methylation of DUSP gene (51) Activation of glucocorticoid receptor with increased BDNF DNA CpG methylation and histone acetylation (52) Long-chain PUFA Alters DNA CpG methylation of BDNF gene (53) Alters CpG methylation genome-wide (54)…”
Section: Epigenetic Modificationmentioning
confidence: 99%